2022
DOI: 10.1039/d2ra00277a
|View full text |Cite
|
Sign up to set email alerts
|

Blocking key mutated hotspot residues in the RBD of the omicron variant (B.1.1.529) with medicinal compounds to disrupt the RBD-hACE2 complex using molecular screening and simulation approaches

Abstract: A new variant of SARS-CoV-2 known as the omicron variant (B.1.1.529) reported in South Africa with 30 mutations in the whole spike protein, among which 15 mutations are in the receptor-binding domain, is continuously spreading exponentially around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…The mutant residue R493 maintains these interactions and additionally forms new interactions with residues D30 and D38 of ACE2 WT ( Supplementary Table S2 ). These new interactions could impact the binding affinity between ACE2-RBD-S, and according to Khan A et al [ 59 ], Q493R mutation leads to more stable interactions with the ACE2 protein. Additionally, in previous studies, it has been shown that Q493R in the RBD spike is significantly associated with Omicron disease severity in patients.…”
Section: Resultsmentioning
confidence: 99%
“…The mutant residue R493 maintains these interactions and additionally forms new interactions with residues D30 and D38 of ACE2 WT ( Supplementary Table S2 ). These new interactions could impact the binding affinity between ACE2-RBD-S, and according to Khan A et al [ 59 ], Q493R mutation leads to more stable interactions with the ACE2 protein. Additionally, in previous studies, it has been shown that Q493R in the RBD spike is significantly associated with Omicron disease severity in patients.…”
Section: Resultsmentioning
confidence: 99%
“…These computational methods have been previously used to design potential inhibitors for SARS-CoV-2. For instance, molecular modelling and simulation-based approaches have been used to target the RBD of the Omicron variant [ 13 ]. Similarly, drug repurposing and molecular screening-based approaches also identified potential small molecules for other proteins such as 3CLpro, PLpro, RdRp, S protein, and NRP1 [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using structural modeling approaches, Abbas et. al reported that Tyr453, Arg493, Ser494, Ser496, Tyr501, and His505 are essential residues targeted by the shortlisted compounds and consequently abrogate the RBD-ACE2 complex in the case of the Omicron variant (B.1.1.529) [ 13 ]. Moreover, the role of Arg403, Asn417, Tyr501, and His505 in the higher infectivity of other variants has also been revealed, thus showing promising results for the inhibition of the PPI complex [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Shafiq et al demonstrated that one of the SARS-CoV-2 variants in Tanzania, the A.30 strain, manifesting the mutations R346K, T478K, and E484K in the Spike-RBD region, aids the virus with immune escape properties [ 51 ]. The Omicron variant, harbours a large number of mutations in the RBD region of the spike protein, including K417N, G446S, Q493R, and Q498R, leading to more stable interactions with the hACE2 protein [ 23 ]. Hence, these hotspot mutations in the Omicron have been considered as a potential target for drug design and repurposing to combat the viral spread [ 24 ].…”
Section: Discussionmentioning
confidence: 99%